Kesadaran Beragama dalam Perspektif Ihsan: Pengalaman Pertaubatan Preman - Heryanto Heryanto (Khazanah Theologia, 2021)
The initial aim was to analyze and evaluate the development of thuggery religious awareness, in order to obtain an overview of the processes, patterns, and factors that influence it. This has done because the subject has changed behavior in religious awareness. This research method has used a qualitative approach, case studies. The sample in this study has used a purposive sampling technique, while the key informants snowball sampling technique. The focus of this research is the religious awareness behavior of thuggery. The data collected by observation, interview, the questionnaire as a guide, and documentation. The results of the study show that religious awareness is a condition that must achieved through the struggle of the person concerned. Strong intrinsic motivation plays a role in religious awareness and repentance. The bad behavior of thuggery has caused by a bad social environment. Family and friends can help someone to repent. The Ulama guidance becomes the way of religious awareness. Childhood religious education plays an important role in fostering adult religious awareness.